PENGARUH PENYULUHAN TENTANG BKB (BINA KELUARGA BALITA) TERHADAP PENGETAHUAN DAN KEAKTIFAN IBU DALAM KEGIATAN BKB - Mitayakuna Stianto (JKM (Jurnal Kebidanan Malahayati), 2021)
Backgroumnd The BKB important to enhance resistance family esp in the role of optimize growth and development for children under five. A lack of understanding of the toddler mother BKB can cause the toddler did not attend BKB. The purpose of research is analyzing the information about BKB effects on knowledge about and liveliness mother in activities in the village in BKB Keras Diwek Jombang district. Methods Design used the model one group post pra-test test design. Population is all mother bulan-36 have children age 3 months. Sampling technique using a technique simple random sampling with large samples from 60 respondents. Independen variable is knowledge and liveliness mother in BKB activities before it was given information about BKB and variable dependen knowledge and liveliness mother in BKB activities after given information about BKB. An instrument use questionnaire sheets. Statistical tests use the wilcoxon on the mistake level (α) 0,05. The results of the study before given information obtained almost all respondents prescience enough 49 as many as percent of respondents (81,7) and the majority of respondents active BKB 33 activities as many as percent of respondents (55), after counseling and have found the majority of respondents prescience enough 44 as many as percent of respondents (73,3) and the majority of respondents in the active BKB 33 as many as percent of respondents (55). The analysis result of knowledge or value p-value 0,005 and liveliness value p-value 0,000 Conclusion  the value of p-value 0,005 and 0,000 < 0.05 , so h0 were rejected and h1 received which would mean there are the information about BKB effects on knowledge about and liveliness mother in activities in the village in BKB Keras Diwek Jombang district. Suggestion Enough mother and knowledge about BKB made mother and capable of change behavior to actively in the BKB. Keywords: information, BKB, knowledge, liveliness ABSTRAK Latar Belakang Program BKB penting untuk meningkatkan ketahanan keluarga khususnya dalam peran mengoptimalkan pertumbuhan dan perkembangan anak balita. Kurangnya pemahaman ibu balita tentang BKB dapat menyebabkan ibu balita tidak mengikuti BKB.Tujuan penelitiannya adalah menganalisis pengaruh penyuluhan tentang BKB terhadap pengetahuan dan keaktifan ibu dalam kegiatan BKB di Desa Keras Kecamatan Diwek Kabupaten Jombang.Metode Desain penelitian menggunakan model one group pra-test post test desain. Populasinya adalah semua ibu yang memiliki anak usia 3 bulan-36 bulan. Teknik sampling menggunakan teknik simple random sampling dengan besar sampel sebanyak 60 responden. Variabel independennya adalah pengetahuan dan keaktifan ibu dalam kegiatan BKB sebelum diberikan penyuluhan tentang BKB dan variabel dependennya pengetahuan dan keaktifan ibu dalam kegiatan BKB sesudah diberikan penyuluhan tentang BKB. Instrumen menggunakan lembar kuesioner. Uji statistik menggunakan uji wilcoxon dengan tingkat kesalahan (α) 0,05.Hasil penelitian sebelum diberi penyuluhan didapatkan hampir seluruh responden pengetahuannya cukup sebanyak 49 responden (81,7%) dan sebagian besar responden aktif kegiatan BKB sebanyak 33 responden (55%), sedangkan sesudah diberi penyuluhan didapatkan sebagian besar responden pengetahuannya cukup sebanyak 44 responden (73,3%) dan sebagian besar responden aktif dalam kegiatan BKB sebanyak 33 responden (55%). Hasil analisa pengetahuan didapatkan nilai p-value 0,005 dan keaktifan  nilai p-value 0,000, karena nilai p-value 0,005 dan 0,000 < 0,05, maka H0 ditolak dan H1 diterima.Kesimpulan ada pengaruh penyuluhan tentang BKB terhadap pengetahuan dan keaktifan ibu dalam kegiatan BKB di Desa Keras Kecamatan Diwek Kabupaten Jombang.Saran Pengetahuan cukup ibu balita tentang BKB menjadikan ibu balita mampu merubah perilaku untuk  aktif dalam kegiatan BKB. Kata kunci: penyuluhan, BKB, pengetahuan, keaktifan